The Role of Caregiver's Feeding Pattern in the Association between Parents' and Children's Healthy Eating Behavior: Study in Taichung, Taiwan - Hung-En Liao; Yueen-Mei Deng (MDPI AG, 2021)
While parenting style has been linked with parent feeding behavior (FB), little is known about the role FB plays in the relationship between parents' eating behavior (PEB) and children's eating behavior (CEB). Based on social learning theory, we hypothesized that children learn to develop healthy CEB by obeying and imitating parents' healthy eating and feeding behaviors, and that FB is the mediator between PEB and CEB. In total, 257 survey responses from parents of children up to 5 years old were included in the study. Results indicated that CEB did not differ by children's age, gender, or birth order; for parents, older age and lower educational levels were associated with less healthy unhealthier FB and PEB. Healthy PEB and FB explained 46.8% and 21.7% of the variance in healthy CEB, respectively. The model confirmed that FB reduced the coefficient of healthy PEB from 0.563 to 0.468 and increased the variance explained from 35.0% to 38.5%. FB was a mediator for PEB and CEB. Discussion covers the complexity of ideal parenting styles and child feeding and their associated effects on CEB in varied environments, including different cultures. We concluded that PEB was the main predictor of CEB, and healthy feeding acted as a mediator.